2007
DOI: 10.1111/j.1469-8749.2007.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional gait comparison between children with myelomeningocele: shunt versus no shunt

Abstract: The aim of this study was to compare functional gait differences between patients with myelomeningocele (MM) who have a ventriculoperitoneal shunt (VPS) with those who do not. Our analyses were adjusted for confounding by age, lesion level, orthotic use, and assistive device use. The Functional Mobility Scale (FMS) was used to compare the shunted group (n=98; 60 males, 38 females; mean age 10y 2mo [SD 3y 11mo]; 73 sacral/19 low lumber/six high lumbar lesion level) with the non-shunted group (n=63; 32 males, 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
2
13
0
4
Order By: Relevance
“…Many other studies reported a similar association [2,3,11,12,16,28]. Davis et al [9] looked at 158 adolescents and reported 84% of the individuals were shunted.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Many other studies reported a similar association [2,3,11,12,16,28]. Davis et al [9] looked at 158 adolescents and reported 84% of the individuals were shunted.…”
Section: Discussionmentioning
confidence: 77%
“…Children with more than four shunt revisions also have a lower functional level [2,11,12,28]. Transition from childhood to young adulthood can be an especially difficult developmental period for those with MM [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has also been applied to children with spina bifida [20]. The FMS is unique because it allows quick, practical scoring of mobility over three distinct distances representing mobility in the home (5 m), at school (50 m), and in the community (500 m).…”
Section: Functional Mobility Scalementioning
confidence: 99%
“…The recurrence of NTDs is greater than 5% for a women having more than one child affected by NTDs. 19,20 Following factors contribute in the epidemiology of NTDs:…”
Section: Epidemiology and Prevalencementioning
confidence: 99%